Sejarah Melayu [English version] - Noriah Mohamed, 1944-; Universiti Kebangsaan Malaysia. Institut Alam dan Tamadun Melayu (Bangi, Selangor : Institut Alam dan Tamadun Melayu, 2003)
This interactive CD highlights the contents of W.G. Shellabear's edition of Sejarah Melayu (Malay Annals). Sounds, graphics and stories are woven together to narrate the tales of Malay kings and warriors. The Malay people have a fascinating history and culture which are profoundly portrayed in intrigue and in drama.
Voice : Amy Seidlitz, Eric Seidlitz.
System requirements: Keperluan Minima untuk PC : Pentium 3 yang berasaskan Komputer Peribadi (PC), Windows 98/NT, 64MB RAM, Pemacu CD-ROM 32 X, Monitor 640 x 480 (16 bits), Sound Card & Speaker. Keperluan Minima untuk Macintosh : Sistem 8.5, 64MB RAM, Pemacu CD-ROM 32 X, Monitor 640 x 480 (16 bits)
Title from container.
Keywords: Malaysia -- History